2006
DOI: 10.20965/jrm.2006.p0160
|View full text |Cite
|
Sign up to set email alerts
|

Development of 6-Axis Material Tester for Measuring Mechanical Spine Properties

Abstract: Because mechanical spine properties having multiple degrees of freedom (DOF) are generally difficult to measure, we developed a parallel 6-axis material tester with hybrid position/force control. We give examples of 6-axis testing and results of material tests using polyurethane rubber and animal spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…For the test, a six-axis material testing machine [ 8 10 ] developed in our laboratory (Fig. 4 ) was used.…”
Section: Methodsmentioning
confidence: 99%
“…For the test, a six-axis material testing machine [ 8 10 ] developed in our laboratory (Fig. 4 ) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Wahba et al experimented with a burst fracture model and reported that the stiffness of the PS model was weaker than that of an intact model [ 5 ]. Lim et al experimented with a discectomy model and reported that the ROMs of the PS model were larger than those of an intact model [ 11 ]. We also performed biomechanical experiments with a facetectomy model and concluded that the ROMs of the PS model were larger than those of an intact model during rotation tests and that insufficient torsional stability might be the cause of pseudoarthrosis and implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…For the biomechanical tests, a 6-axis material testing machine developed in our laboratory that allows motion with 6 degrees of freedom was used ( Figure 2 ) [ 11 ]. In this study, we performed both a bending test (anterior, right-anterior, right, right-posterior, posterior, left-posterior, left, and left-anterior bending) and a rotation test (right and left rotation).…”
Section: Methodsmentioning
confidence: 99%
“…For the tests, a six-axis material testing machine developed in our laboratory was used (Fig. 3 ) [ 15 ]. This testing machine adopts a parallel mechanism.…”
Section: Methodsmentioning
confidence: 99%